A phage virus-based electrochemical biosensor for highly sensitive detection of ovomucoid. (1st June 2022) - Shin, Jae Hwan; Park, Tae Jung; Hyun, Moon Seop; Park, Jong Pil
Highlights: We have designed, fabricated and evaluated an electrochemical phage sensor for detection of ovomucoid. Introduction of EDC/NHS and SPDP coupling chemistry was achieved to chemically attachment of whole phage. Both chemically encoded cyclic and linear peptides-displayed phage sensors were evaluated by SWV and EIS. Our developed phage sensor had good performance in a complexed real sample matrix Abstract: Whole peptide-displayed phage particles are promising alternatives to antibodies in sensor development; however, greater control and functionalization of these particles are required. In this study, we aimed to identify and create highly sensitive and selective phage-based electrochemical biosensors for detecting ovomucoid, a known food allergen. Phage display was performed using two different phage libraries (cyclic and linear form of peptides), which displayed affinity peptides capable of binding specifically to ovomucoid. Throughout the biopanning, two phage clones that displayed both peptides (CTDKASSSC and WWQPYSSAPRWL) were selected. After the characterization of their binding affinities, both whole phage particles were covalently attached to a gold electrode using crosslinking chemistry (MUA-EDC/NHS and Sulfo-LC/SPDP); the developed phage sensor was characterized using cyclic voltammetry (CV), square wave voltammetry (SWV), and electrochemical impedance spectroscopy (EIS). The cyclic peptide-displayed phage sensor modified using EDC/NHS chemistry exhibited significantly better binding affinity ( K d = 2.36 ± 0.44 μg/mL) and limit of detection (LOD, 0.12 μg/mL) for ovomucoid than the linear phage sensor, resulting in good reproducibility and recovery, even in an actual egg and white wine samples. This approach may provide an alternative and more efficient way of sensing food allergens with desirable sensitivity, selectivity, and feasibility in food diagnostic applications.